Peningkatan Produktivitas Ternak Sapi Melalui Penerapan Teknologi Inseminasi Buatan Bagi Peternak Di Desa Pekalobean, Kecematan Anggeraja, Kabupaten Enrekang - Agustan; Muhammad Farid; Ita Puspitasari (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service activity aims to improve the understanding of beef cattle farmers about AI technology in Pekalobean Village, Anggeraja District, Enrekang Regency. On December 13, 2024, local farmers participated in the activity initiated by the Thematic KKN students of Muhammadiyah Bone University. The Thematic KKN Program of Muhammadiyah Bone University in Pekalobean Village aims to empower cattle farmers by utilizing Artificial Insemination (AI) technology. The application of this material directly uses teaching aids to teach AI, livestock nutrition, and maintenance management. The activity, which also became a place for discussion and sharing experiences, was actively participated by farmers. This training is expected to increase livestock production and the financial welfare of farmers, as well as help them manage their livestock businesses independently